Analisis Waktu Respon Hidrolik pada Simulator Rough Terrain Crane Berbasis 3D Printing: Hydraulic Response Time Analysis on a 3D Printing-Based Rough Terrain Crane Simulator - Muhamad Safta Aji; Sriyono; Tatang Permana (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study aims to analyze the hydraulic response time of a 3D printing-based Rough Terrain Crane simulator developed as a learning medium in Automotive Engineering Education. The simulator was designed to represent the working principles of a hydraulic system in a telescopic boom mechanism, allowing students to directly observe the operation of hydraulic actuators. The research employed an experimental method by applying load variations to the telescopic boom and measuring the system response time from the operation of the directional control valve until the hydraulic cylinder began to move. The applied load variations were 0 g, 100 g, 200 g, 300 g, and 400 g, with three repetitions for each test. The collected data were analyzed using descriptive quantitative analysis based on the average response time for each load variation. The results showed that the hydraulic system response time increased as the applied load increased. The average response time was 1.84 seconds under no-load conditions and increased to 3.31 seconds at a load of 400 g. These findings indicate that greater loads require higher hydraulic force and pressure to move the telescopic boom, resulting in longer actuator response times. The developed simulator successfully demonstrated the fundamental characteristics of hydraulic systems and has potential as an interactive learning medium for teaching heavy equipment hydraulic systems.